ANALISIS STRATEGI MEMPERTAHANKAN KEARIFAN LOKAL RAMAH LINGKUNGAN DALAM USAHATANI PADI SAWAH VARIETAS LOKAL DI DESA KEMUNING MUDA KECAMATAN BUNGA RAYA KABUPATEN SIAK - Kiki Prayogo; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research was conducted in rural districts Bungaraya young kemuning district siak. This study was conducted to identify local wisdom that ever existed and still exists today, and analyzes the local wisdom that is environmentally friendly and any strategy in defending indigenous rice crops. The purpose of this study is to identify the local wisdom that once existed in the agricultural environment, analyzing the application of local wisdom that is still going on paddy fields in the district hibiscus, analyze the strategy of maintaining an environmentally friendly local wisdom in the use and management of rice paddy fields. The method used is in qualitative research methods used to examine the condition of natural objects. This sampling technique using snowball sampling techniques in sequence to obtain the saturation point of a question. depth interviews with respondents and record it in the form of voice recorder that uses a questionnaire that has been made before. Local knowledge is a form of knowledge, beliefs, rules. customs, and habits performed by a community that supports, norms and cultural values that have been there earlier and was sent down by ancestors to be passed on to children and kemenkannya in running everyday life. in this study there is a local wisdom that still on the run, even though the procedure, the customs and rules is not running as before.Keywords: Local Wisdom, Environmen, Local knowledge